Influencia del bullying en la deserción escolar en los estudiantes de la Institución Educativa Boyacá (2017)
This research aimed to determine the bullying influence on school dropout at Boyacá Institute in Ibague city in 2016. The question is how bullying influences students who dropped out school. For doing this, a data verification was done, some of the results were found at the school itself, the analysis was confronted against the evidenced documents. A methodological design was used in order to get into the mixed model, making a data collection in an analytical way based on documents, records, observational records, conditional sign up sheets and annotations, which in turn managed to allow a quantifiable students development facing the ones who dropped out. It is essential to mention that a format was created it mentions the bullying categories and it was used to contrast the descriptive information found in the aforementioned documents; it was also complemented by a bibliographical compilation of scientific articles and research focused on the subject as such. However, bullying in the institution is 53.5%, directly affecting the school dropout with 23.3% of the 43 subjects in the sample; concluding, bullying is a real phenomenon in the institution even when it only affects directly dropout, ie, the percentage is lower than expected according to theoretical background and a priori school identification